Stochastic colonisation dynamics can be a major driver of temporal β diversity in Atlantic Forest coastal stream communities - Saito, Victor S. (2021)
Biodiversity is structured in space and time, yet our understanding about the temporal variation of biological communities is still limited. Recent work suggests that temporal β diversity should be lowest in unpredictable systems with low seasonality, as expected for tropical ecosystems. However, this hypothesis remains largely unexplored. Here, we analysed the temporal dynamics of Atlantic Forest coastal stream caddisfly assemblages sampled simultaneously along four years, resulting in 99 unique site-time combinations. Given that the region we studied is expected to have low climatic seasonality and low environmental harshness, we expected to find: (1) unseasonal variation in community composition; (2) equal contribution of nestedness and turnover to β diversity; (3) weak correlation between variation in community composition and in environmental variables; and (4) temporal β diversity similar to that expected by neutral dynamics. Using wavelet analysis we found that, in spite of general temperature stability, precipitation was highly seasonal but unpredictable at the monthly scale. We found high temporal β diversity, with a larger contribution of nestedness due to an overall decrease in abundance and diversity during months characterised by heavy rain events. We also found that community composition was moderately structured in space, suggesting that both local in-stream characteristics and dispersal limitation drive community reassembly after heavy rain events. Null model analysis indicated that observed short-term β diversity was not distinct from that expected by chance (i.e. produced by null simulations). This suggests an important role of stochastic colonisation and dispersal limitation in the temporal organisation of Atlantic Forest stream assemblages. Since heavy rain events strongly disassemble communities that are then randomly recolonised, and considering the current scenario of climate change, increased extreme events of precipitation could lead to unpredictable changes in biodiversity in tropical regions.